Design of LCL and LLCL filters for single‐phase grid connected converters. Issue 9 (1st July 2016) - Sanatkar‐Chayjani, Majid; Monfared, Mohammad
Abstract : Compared with the traditional L filters, the high order LCL and LLCL filters for grid integration of voltage source converters offer better switching harmonic attenuation even with smaller passive elements. However, the inherent resonance of the high order filters complicates the control of the converter and also the design of filter parameters, especially at presence of digital delays and grid impedance variations. This study proposes a simple design procedure for the LCL and the LLCL filters of a delay‐based stabilised converter that satisfies the predefined constraints on the converter current ripple, grid current harmonics and the reactive power of the capacitor and at the same time, ensures adequate stability of the simple single loop current control against the resonance. Moreover, the effect of grid impedance on the filter performance and controller stability is taken into account, thus the proposed method is robust against a wide range of grid impedance variations. Experimental results for a 3 kW test rig under steady state and transient conditions confirm the effectiveness of the proposed filter design algorithm.